Electrical conductivity and relaxation processes in V2O5 nanorods prepared by sol–gel method. Issue 9 (8th June 2015) - Prześniak‐Welenc, M.; Szreder, N. A.; Winiarski, A.; Łapiński, M.; Kościelska, B.; Barczyński, R. J.; Gazda, M.; Sadowski, W.
<x xml:space="preserve">Abstract</x> Properties of high purity V2O5 nanorods prepared by a sol–gel method are presented. The studied materials were characterized by: X‐ray diffractometry (XRD), scanning electron microscopy (SEM), and X‐ray photoelectron spectroscopy (XPS). The electrical impedance was measured as a function of temperature and frequency. The obtained results show that the electrical conductivity increases with increasing temperature. The d.c. conductivity exhibits activation energy of 0.23 eV (±0.01). Two dielectric relaxation processes were observed and attributed to the conductivity of grain boundaries and grains interiors